Material and Structural Properties of Fiber-Reinforced Resin Composites as Thin Overlay for Steel Bridge Deck Pavement - Hui Zhang; Chengqi Zhou; Kuan Li; Peiwei Gao; Youqiang Pan; Zhixiang Zhang (Advances in Materials Science and Engineering)
Fatigue cracks are main damages to steel bridge deck pavement with thermosetting epoxy asphalt. By combining a high-toughness resin material with fiber woven fabrics, this study formed an ultrathin overlay of fiber-reinforced high-toughness resin to improve cracking resistance of pavement. Through theoretical measurement and bending test, this research studied change laws of bending and tensile properties of epoxy asphalt concrete after fiber reinforcement and analyzed bending strength and the maximum failure strain of beams at different temperatures. Moreover, the reinforcing effects of different fibers were discussed. It is found that bending strength, maximum failure strain, and stiffness modulus of the beams with epoxy asphalt are improved after fiber reinforcement. With the decrease of temperature, after fiber reinforcement, the mode of bending failure of the epoxy asphalt mixture (EAM) changes from brittle fracture into shear failure, accompanied with significant yield phenomenon. Furthermore, organic carbon fiber is sensitive to influences of temperature, while glass fiber is least sensitive to temperature.